Judge Decision Analysis on Civil Cases Against Counterfeiting Land Deed Decision Number 350 K/Pdt/2017 Mataram District Court - Fergi Firosa Akbar (Universitas Negeri Semarang, 2022)
Indonesia is a legal state, in the execution of a judge is an object that is very important for a trial. In Indonesia alone the practice of fraud and manipulation is still common and often encountered in a trial, the duty of a judge who should be neutral and decide a case with as fair as possible can often be manipulated by the bribery process of a suspect. the power of a judge alone is set in the law of the judicial power law number 48 of 2009. There it has been explained everything about the duties and authority of a judge and how to be a just judge and then can put a suspect into a subject rather than a object. Often in finding a judge actually complicates a case that is actually trivial and gives a burdensome decision for the little people and even facilitate a big case with a suspect of important people, a concept that is not denied a thing that we often see in law.